On emotional aspects in Mission‐Oriented Opportunistic Networks. Issue 3 (1st September 2014) - Misra, Sudip; Saha, Barun Kumar
Abstract : In Mission‐Oriented Opportunistic Networks (MOONs), the human users, who possess the mobile devices, also participate as part of the network. In this study, the authors study an aspect of human–network interplay in MOONs, by considering the effects of human emotions on the network operations. This study differs from the related existing works, which focus on detecting emotions of the users based on their activities, for example, their smart phone usage patterns. The study uses Meftah's computational model of the emotions, which itself is based on Plutchik's model. The authors model the current emotion of any user as a function of the individual's previous state of emotion and the content of the messages received by them. Specifically, the authors consider how the variation in individual emotions affect the traffic generation rate in the network. Further, they model the scenarios in which the users switch off their devices' radios, and their effects on the message delivery ratio. The results of performance evaluation show that the delivery ratio of the messages tends to zero because of increased traffic load and inactivity of the devices' radios, which, in turn, calls for efficient traffic management and forwarding schemes.